2019
DOI: 10.1186/s13046-019-1332-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long non-coding RNA MACC1-AS1 promoted pancreatic carcinoma progression through activation of PAX8/NOTCH1 signaling pathway

Abstract: Background Accumulated evidences have demonstrated that long non-coding RNAs (lncRNAs) are dysregulated and correlate with the pathophysiological basis of malignant tumors. The objective of this research is to uncover the possible molecular mechanism of MACC1-AS1 regarding the regulation of pancreatic carcinoma (PC) metastasis. Methods lncRNA microarray and qRT-PCR were applied to identify differentially expressed lncRNA profile in PC. The function and role of MACC1-AS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…4 lncRNAs act as signaling molecules, scaffolds, and instructors, and exert their influence at several levels including transcription, post-transcription, and translation. 5 In recent years, abundant evidence has revealed that anomalous expression of lncRNAs such as HOXD-AS1, H19, CASC9, and NORAD [6][7][8][9] may drive the pathogenesis of breast cancer. In addition, anomalous expression of lncRNAs may serve as a biomarker for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…4 lncRNAs act as signaling molecules, scaffolds, and instructors, and exert their influence at several levels including transcription, post-transcription, and translation. 5 In recent years, abundant evidence has revealed that anomalous expression of lncRNAs such as HOXD-AS1, H19, CASC9, and NORAD [6][7][8][9] may drive the pathogenesis of breast cancer. In addition, anomalous expression of lncRNAs may serve as a biomarker for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Higher expression of lncRNA MACC1-AS1 correlates with the lung metastasis of gastric cancer cells, and MACC1-AS1 is elevated under metabolic stress and facilitates metabolic plasticity by increasing MACC1 mRNA expression and strengthening glycolysis and anti-oxidative abilities via the AMPK/Lin28 pathway (121). LncRNA MACC1-AS1 is also upregulated in pancreatic cancer and related to poor prognosis, and its knockdown inhibits the metastasis of pancreatic cancer cells by upregulating the expression of PAX8 (paired-box gene 8), which plays a role in activating NOTCH1 signaling and promoting cell aerobic glycolysis (122).…”
Section: Lkb1-amp Activated Protein Kinase Pathwaymentioning
confidence: 99%
“…Among these, long non-coding RNAs (lncRNAs), which are over 200 nucleotides in length, have emerged as key regulators in biological processes for their diverse and complex work mechanisms [4]. LncRNAs have been reported to affect an array of cellular functions, such as cellular growth, apoptosis, migration and invasion, as well as EMT progression [5][6][7][8]. Also, increasing lncRNAs have been detected to be aberrantly expressed in cancers.…”
Section: Introductionmentioning
confidence: 99%